(3GdJWhQ GdCcGOjej hGdEYOGO ddegfI GdCcGOjejI Hjf JMOjGJ GdYhdeI heJWdHGJ GdJOhjd (B/s - (3GdYLej, eMeO MSjfs ((3GdEScfOQjI(B: s (3GdecJHI GdYUQjI(B, s, 2007)
(3jVe GdegfI GdCcGOjejI hYVh gjFI GdJOQjS, JMOjGJ GdYhdeI heJWdHGJ JOhjd GdJYdje GdLGeYj, GJLGgGJ GdJWhQ GdCcGOjej ddLGeYI, GdegfI GdCcGOjejI HGdLGeYGJ GdeUQjI efXhQ JWHjbjs
(3GdeQGLY U(B.146s
Keywords: (3GdCcGOjejGJs; (3GdJYdje GdYGdjs; (3GdLGeYGJ hGdcdjGJs; (3Gdegfs